2023
DOI: 10.1097/ico.0000000000003363
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Age on the Characteristics of Corneal Nerves and Corneal Epithelial Cells in Healthy Adults

Jia Ying Chin,
Chang Liu,
Isabelle Xin Yu Lee
et al.

Abstract: Purpose: The aim of this study was to investigate age-related changes in corneal nerves and corneal epithelial cell parameters and to establish age-adjusted reference values. Methods: A total of 7025 corneal nerve images and 4215 corneal epithelial images obtained using in vivo confocal microscopy from 281 eyes of 143 healthy participants were included. Seven corneal nerve parameters and 3 corneal epithelial cell parameters were quantified using 2 autom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…11 Additionally, Chin et al found a decline in corneal nerve fiber length and density in patients aged 65 or older, further emphasizing the importance of considering age-related factors in ocular health. 12 These studies highlight the need for more research on how aging affects the corneal nerve and overall ocular surface health.…”
Section: Aging and The Corneamentioning
confidence: 99%
See 1 more Smart Citation
“…11 Additionally, Chin et al found a decline in corneal nerve fiber length and density in patients aged 65 or older, further emphasizing the importance of considering age-related factors in ocular health. 12 These studies highlight the need for more research on how aging affects the corneal nerve and overall ocular surface health.…”
Section: Aging and The Corneamentioning
confidence: 99%
“…2024;43(4):409. doi:10.1097/ICO.0000000000003363. 12 Prospective, randomized, comparative study Reduced endothelial cell density with age. Hepokur M, Bulut Kizilay E, Durmus E, Aykut V, Esen F, Oguz H. The influence of corneal incision size on endothelial cell loss and surgically induced astigmatism following phacoemulsification cataract surgery.…”
Section: Aging and The Corneamentioning
confidence: 99%